2017
DOI: 10.1063/1.4979317
|View full text |Cite
|
Sign up to set email alerts
|

Control of circularly polarized THz wave from intrinsic Josephson junctions by local heating

Abstract: This paper reports a practical method of generating circularly polarized terahertz (THz) waves from intrinsic Josephson junctions (IJJs) and controlling their polarization states by external local heating. We theoretically find that a mesa-structure IJJ whose geometry is almost square can emit circularly polarized THz waves by local heating of the mesa. Moreover, we demonstrate that the polarization states of the THz waves change dramatically with the local heating position. Our results indicate that the use o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Controlling of the polarization is of especial importance in many applications of THz waves, for example in THz imaging, sensing, spectroscopy, high-speed and wireless telecommunication, etc [73][74][75][76]. The IJJ THz sources can be an excellent THz source for these purposes because (i) they have a unique ultra-wideband tunability and (ii) their emission intensity can be (internally and externally) thermally controlled [77][78][79][80].…”
Section: (Iv-iii) Polarization Control Of Ijj Thz Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlling of the polarization is of especial importance in many applications of THz waves, for example in THz imaging, sensing, spectroscopy, high-speed and wireless telecommunication, etc [73][74][75][76]. The IJJ THz sources can be an excellent THz source for these purposes because (i) they have a unique ultra-wideband tunability and (ii) their emission intensity can be (internally and externally) thermally controlled [77][78][79][80].…”
Section: (Iv-iii) Polarization Control Of Ijj Thz Sourcesmentioning
confidence: 99%
“…IJJ THz devices with a rectangular cavity are known to emit linearly polarized light [26]. Asai et al first theoretically demonstrated that circular polarized (CP) THz waves can be emitted from IJJ THz emitters that are locally heated by an external heat source, such as a laser [79]. This is because, in a square cavity, the laser would induce an inhomogeneity in the critical current density, that results in the excitation of the EM cavity TM (1,0) and TM (0,1) modes, whose polarizations are orthogonal to each other, so CP can be generated by a mixture of those two excited modes.…”
Section: (Iv-iii) Polarization Control Of Ijj Thz Sourcesmentioning
confidence: 99%
“…The IJJ-THz emitters based upon superconducting Bi2212 single crystals have intensively been developed both experimentally and theoretically. [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] So far, the best performance has been achieved within the frequency range from 0.3 to 11 THz, [11][12][13]34,35,39 with the maximum output power of $30 lW, [31][32][33][34]39 and with a spectral width of the coherent and continuous emission of THz radiation that is generally less than 0.5 GHz, and under appropriate conditions, it was reported to be narrower than 23 MHz and possibly even 6 MHz. [23][24][25] Furthermore, a synchronized operation of an array of three such emitters was reported to yield the greatly enhanced power of 610 lW.…”
Section: Introductionmentioning
confidence: 99%
“…Waves emitted from rectangular IJJ-based sources have been known to be linearly polarized [2]. However, recent numerical studies [14,25,26] have proposed the possibility of realizing circularly polarized emissions from IJJ devices. This paper reports the first experimental demonstration of the generation of circularly polarized sub-THz waves from a monolithic source-a superconducting IJJ stack-wherein the ellipticity and evolution direction are tuned by mesa shape and bias conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these devices, IJJ-based sources can cover wider frequency ranges, which are unattainable by other THz sources [4]. Furthermore, the emission intensity of IJJ-based devices can also be thermally controlled, both internally [12,13] and externally [14,15]. By applying a direct current (DC) voltage (𝑉 𝑏 ) across the c-axis of IJJs stacked in a mesa form, a high frequency (HF) current is generated along with emission of sub-terahertz radiation at the Josephson frequency given by 𝑓 𝐽 = (2𝑒𝑉 𝑏 /ℎ𝑁), where ℎ, 𝑒, and 𝑁 denote the Planck constant, elementary charge, and number of contributing IJJs, respectively.…”
Section: Introductionmentioning
confidence: 99%